Book Review. Women After All: Sex, Evolution, and the End of Male Supremacy - Mala Hernawati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
Konner’s Women After All begins with thequotation from Elizabeth Cady Stanton, a leading figure of the American suffragist, “Because man and woman are the complement of one another, we need woman’s thought in national affairs to make a safe and stable government.” This quotation was a part of her address to the National Woman Suffrage Convention in Washington D.C., on January 19, 1869. However, the idea on equality between man and woman is just a starting point toward Konner’s thesis which is far beyond equality: women are not equal to men – they are superior to men.